Impact of Nutritional Status on Survival in Head and Neck Cancer Patients After Total Laryngectomy. (21st April 2022) - Santos, Adriana; Santos, Izabella Costa; dos Reis, Patrícia Fonseca; Rodrigues, Viviane Dias; Peres, Wilza Arantes Ferreira
Abstract: Malnutrition is an important prognostic indicator of laryngeal squamous cell carcinoma. Retrospective study with head and neck cancer patients who underwent total laryngectomy. 243 patients of both sex were evaluated. The univariate analyses demonstrated an increased risk of death for the patients with greater weight loss, hypoalbuminemia, radiotherapy as an initial treatment, salvage surgery, and radical neck dissection. In a Multivariate Cox regression, older age ( p = 0.03, 95% confidence interval [CI] 1.003–1.06, hazard ratio [HR] 1.029), Nutritional Risk Index ≤100 ( p = 0.008, 95% CI 1.18–3.12, HR 1.921) and adjuvant radiotherapy ( p = 0.029, 95% CI 0.31–3.12, HR 0.544) demonstrated prognostic significance in survival. Nutritional status is a modifiable variable and these findings highlight the need to adoption of simple nutritional assessment methods routinely during the treatment of head and neck cancer patients, in order to help improve prognosis after surgery.